Analysing the manipulation of the youths, election violence and democratic retrogression in South Africa - Ibrahim Yusuf Didamson (African Journal of Political Science)
Since the introduction of elective democracy in the 1990s, South African youths have played a significant role in the democratic process. Sadly though, while some are building from the past experiences of the 1976 youths, others are deeply engrossed into crimes, violence, and thuggery. Several factors have been identified as the drivers of South African youths into different forms of criminalities. Prominent among them are the pauperization of the youths by the state, unemployment, and their manipulation by the political elite. Rather than replicating the character of the youths of the 1970s who fought for better education and life as well as the freedom of the black population during the dark days of apartheid, some youths have taken to drugs, election violence while others have become personal security to top politicians owing to difficult economic hardship. The paper opined that to address this anomaly, there is the need for the South African youths to rediscover themselves by positioning themselves into politics and never expect the government to empower them cheaply. Also, the voice of the youths must not only be heard but be felt through character, integrity, disciplined and quality leadership. Through this, they will be able to shape policies and direction of government, and the future of many unborn generations. The qualitative research techniques were used for this study. Data was collected through interviews and focus group discussions in five sampled locations in KwaZulu-Natal. The thematic and inductive method of analysis was used in aiding the analysis of the generated data.